Development and Prospect of Electrodeposited Technology of Tin - Cobalt Alloy - ZHANG Qi, ZHANG Ce, YI Juan, ZHAO Tao, MAO Zu-guo, ZHANG De-zhong, REN Xing-hai, TAO Ming (Cailiao Baohu, 2021)
Hexavalent chromium coatings are widely used for their excellent decorative and functional properties, but the related environmental and health problems should not be underestimated. In order to reduce the environmental pollution caused by hexavalent chromium, tin-cobalt alloy plating technology has been developed and used to replace the decorative chromium coatings. Based on the related domestic and foreign research progress in recent years, the research history and the current research status of tin-cobalt alloy plating technology were reviewed, and the typical schemes of tin-cobalt alloy plating process in different periods and fields were introduced in detail. Meanwhile, the types, characteristics and development of tin-cobalt alloy plating solutions were also summarized, including the characteristics and deficiencies of pyrophosphate, gluconate, citrate and other systems which were studied a lot in recent years. And it was pointed out that the alloy coatings obtained from these systems had high cobalt content, their appearances and performances were similar to chrome plating and the process was more environmental friendly, which were expected to replace chrome plating. Finally, the currently facing main problems of the tin-cobalt alloy plating technology were discussed, the future development trend was prospected and it was also proposed that the cathode material of lithium ion battery would become a research hotspot related to tin-cobalt alloy plating technology.